Measuring climate knowledge: A systematic review of quantitative studies - Maruša Lubej; Žiga Petraš; Andrej Kirbiš (iScience)
Summary: Climate change is a pressing issue that necessitates a climate-literate population. This systematic literature review investigates how climate knowledge, a key component of climate literacy, is measured in scientific research. Analysis of 92 studies reveals that climate knowledge is primarily assessed as objective knowledge (facts and evidence). A minority of studies measured subjective knowledge. Most often, the target population was general adult population, followed by students and teachers. Furthermore, most studies are concentrated in North America and Europe, while climate knowledge remains underexplored in other regions. This review highlights the lack of consistency in the measurement of climate knowledge, particularly in defining its dimensions. Our findings underscore the need for future research to focus on developing a standardized, reliable, valid, and comprehensive instrument for measuring climate knowledge. This would enable the comparison of findings across different regions and populations.